Blended Literacy: Post-Pandemic Literacy Strategies at Integrated Madrasah Tsanawiyah - Redite Kurniawan; Muhammad Yunus Abu Bakar; Ah. Zakki Fuad (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2023)
Due to the post-pandemic, madrasahs need effective literacy strategies to cope with the challenges posed by the situation. While some madrasahs may have implemented these strategies, they may be constrained by common issues. This study aims to analyze blended literacy activities to improve the literacy program at Integrated Madrasah Tsanawiyah after the Covid-19 pandemic. This research used a qualitative approach with a case study type. Data were collected through observation, interviews, and documentation. The data was analyzed by organizing, reducing, and interpreting data. Based on the study results, it is evident that the blended literacy strategy used at Integrated Madrasah Tsanawiyah combines offline activities (print-based and face-to-face) and online activities (technology and internet-based) in student literacy activities, both within and outside the madrasah to improve the quality of madrasah literacy. This study can provide a framework for other madrasahs or educational institutions to develop their blended activities literacy programs, particularly during times of crisis when traditional teaching methods may not be feasible.